30 ans d’articles dans Mappemonde. Une exploration par les mots-clés et les résumés - Grégoire Le Campion; Olivier Pissoat; Laurent Jégou; Matthieu Noucher (M@ppemonde)
For the journal’s 30th birthday, Mappemonde has explored its content through the analysis of 964 articles published between 1986 and 2017. Our automated approach focuses on keywords and abstracts, including the production of expressive visual representations. While outlining the evolution of research published in this journal on geographical images and forms of the territory, we have also underlined the methodological limits of such an approach. Data is now open access to allow everyone to continue and improve the study.